ANALYSIS AND MODELING OF FLYBACK CONVERTERS USING WIDEBAND SEMICONDUCTOR DEVICES BASED ON GALLIUM NITRIDE - ARSENIUK, DMYTRO; ZINKOVSKYI, YURI (Herald of Khmelnytskyi National University. Technical sciences, 2023)
This paper presents the findings from a study on AC-DC power converters, specifically focusing on those where the power element is a gallium nitride (GaN HEMT) based field-effect transistor. Flyback converters are employed in the development of pulsed power supplies, aiming for high efficiency and minimal heat generation, which are key objectives in contemporary power electronics. The study primarily addresses the challenge of switching losses in power transistors at elevated switching frequencies, an area where silicon-based field-effect transistors have nearly reached their developmental zenith. The incorporation of a wideband power transistor based on gallium nitride in the converter has been shown to enhance device stability by achieving low switching losses. This advancement enables operation at higher frequencies. Additionally, GaN HEMTs exhibit shorter recovery times compared to other power switch types, collectively boosting the energy efficiency of power converters and facilitating a reduction in device size. A comprehensive computer model of the converter was constructed in the LTSpice XVII, incorporating detailed component parameters. The simulation yielded data on currents and voltages across the GaN transistor, power dissipation in the transistor, and the device’s output characteristics. The simulation results indicate a significant reduction in dynamic losses and pulsations on the transistor, coupled with a low level of heat generation. These findings underscore the potential of using wide bandgap devices in the creation of high-frequency energy converters. Such converters are particularly suited for applications requiring compact power sources, such as in small aircraft systems and telecommunication networks.